Vascular birthmarks: A hidden world behind a word - Carlo Gelmetti (Wolters Kluwer Medknow Publications, 2018)
A confusing nomenclature concerning the subject of vascular birthmark and angiomas lead (and leads!) to the consequence that parents with children affected by this kind of disorders become medical nomads, and therefore, the best treatment, when available, is frequently postponed. The concept of maternal imprint that began to crumble in the XVIII century is, unfortunately, still widespread. While a maternal responsibility as it has been conceived in the past has been definitively excluded, the pivotal classification proposed by John Mulliken that divides vascular anomalies in vascular tumors and vascular malformations is practically very useful. The rapid progress of genetic studies has explained to medical community a huge number of genotype-phenotype correlations, and it will individuate new forms in the next future. Understanding the biology of vascular birthmarks is a fundamental step forward to implement effective and specific drugs for specific forms. Discoveries by serendipity occur but are rare.